Farmer’s Knowledge About Moth bean Production Technology in Arid Zone of Rajasthan - Singh, Bhagwan (Annals of Arid Zone, 2016)
The study was conducted in two panchayat samitis of Jodhpur district of Rajasthan. From each panchayat samiti three villages and from each village 30 moth bean growing farmers each, 10 marginal, small and large were selected randomly. The total number of farmers were 60 marginal, 60 small and 60 large. The study revealed that majority of the marginal, small and large farmers’ possessed fair knowledge regarding seed technology of moth bean and poor knowledge regarding fertilizer and plant protection technology. Over all majorities of the marginal, small and large farmers possessed fair knowledge regarding moth bean production technology. Out of twelve variables age of the marginal, small and large farmers was negatively and significantly correlated with knowledge of moth bean production technology while caste, education, social participation, mass media exposure, contact with extension agencies and infrastructure facilities were positively and significantly correlated with knowledge. The education of the farmers was found most important predictor of knowledge.